2020
DOI: 10.1177/0015732520970426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trade Openness and Climate Change on Food Productivity in Nigeria

Abstract: Liberal trade regimes could help improve food productivity if environmental concerns such as adverse weather conditions that affect agriculture are addressed. This issue has not received adequate empirical scrutiny as linear models dominate extant literature. In this article, we check whether accounting for trade and climate change asymmetries is important in explaining food productivity in Nigeria. Using a nonlinear autoregressive distributed lag (ARDL) model, the existence of asymmetry was established in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…In turn, it benefits food security as lower prices make food more accessible, while a greater variety of food options improves food stability by reducing reliance solely on domestic production. This study supports evidence from previous observations (Adamchick & Perez, 2020;Dithmer & Abdulai, 2017;Fusco et al, 2020;Marson et al, 2022;Shuaibu, 2021;Sunge & Ngepah, 2022), These studies found that trade openness enhances food security. Trade openness improves food security because international trade plays a crucial role in stabilizing agricultural production, not only at a global level but also within nations or regions.…”
Section: The Effects Of Trade Openness and Economic Uncertainty On Fo...supporting
confidence: 92%
See 1 more Smart Citation
“…In turn, it benefits food security as lower prices make food more accessible, while a greater variety of food options improves food stability by reducing reliance solely on domestic production. This study supports evidence from previous observations (Adamchick & Perez, 2020;Dithmer & Abdulai, 2017;Fusco et al, 2020;Marson et al, 2022;Shuaibu, 2021;Sunge & Ngepah, 2022), These studies found that trade openness enhances food security. Trade openness improves food security because international trade plays a crucial role in stabilizing agricultural production, not only at a global level but also within nations or regions.…”
Section: The Effects Of Trade Openness and Economic Uncertainty On Fo...supporting
confidence: 92%
“…Interestingly, these effects are primarily attributed to the import component rather than income, indicating a direct influence. Several other studies, such as those by Adamchick & Perez (2020); Dithmer & Abdulai (2017); Fusco et al (2020); Shuaibu (2021); Sunge & Ngepah (2022) have also yielded similar results, demonstrating the positive influence of trade openness on food security. However, it is worth noting that not all studies reach the same conclusions.…”
Section: Literature Reviewsupporting
confidence: 63%
“…The plausible explanation is that if environmental concerns are addressed, liberal trade policies improve the productivity of agriculture. For instance, by regulating the effects of adverse weather conditions on crops, trade openness among countries can help boost food production (Shuaibu, 2021 ). Besides, we find that increased farmed cereal area significantly promotes cereal production.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Following Huh and Park (2013) on the relevant regressors for Food Prices (fp) in this study, I specify fp = f (exr, ms, ir, to, cc) where (i) the Exchange Rate (exr) against the dollar can affect local food prices by altering import prices, (ii) Money Supply (ms) is included to reflect inflationary pressures on the general price level, (iii) Interest Rate (ir) is incorporated because a change in interest rate changes demand for money and hence food prices (high interest rates reduce firms' desire to carry inventory (Frankel 2014), and (iv) International trade (to) is included, first because Nigeria is an open economy and second, because high food prices could engender increased import and vice versa (Lee et al 2021). Finally, (v) Climate Change (cc) variable (average temperature) is included because climate change affects food production and food prices (Shuaibu 2020).…”
Section: Model 1 (Food Prices As Dependent Variable)mentioning
confidence: 99%